Degradation of polylactic acid/polybutylene adipate films in different ratios and the response of bacterial community in soil environments. (15th November 2022) - Zhang, Yalin; Gao, Wei; Mo, Aoyun; Jiang, Jie; He, Defu
Abstract: Biodegradable plastic mulch film (BDM) is an environmentally friendly alternative to conventional polyethylene mulch, and has been growingly used in agriculture. However, practical degradation performance of BDM, especially the widely used type of blended polylactic acid (PLA)/polybutylene adipate (PBAT) in different ratios, and microbial alteration in soil environments, remain largely unrevealed. In this study, four types of BDM blended with 40–80% PLA and 20–60% PBAT were comparatively investigated through microcosm soil incubation experiments for 105 days, and combined with conditions of different soil moisture or pH. Microbiome within film-surrounding soil were assayed using 16 S rRNA high-throughput sequencing. Results showed a trend of increasing degradation efficiency with the increase of PLA proportion, and 70% PLA and 30% PBAT group presented the highest weight loss rate, i.e., 60.16 ± 5.86%. In addition, degradation and aging of PLA/PBAT varied among different soil moisture and pH values. A moderate moisture, i.e., 60% and a neutral pH7.0 caused significantly high degradation efficiency compared to other moisture or pH conditions. Moreover, bacterial abundance and community structure in the surrounding soil were related to soil moisture and pH. PLA/PBAT incubation treatment induced a remarkable increase in abundance of degradation-related species Pseudomonas and Sphingomonas . Bacterial richness and diversity in soil correspondingly respond to ratio-different PLA/PBAT's degradation under moisture/pH-different conditions through a redundancy analysis. Altogether, these findings indicate that practical degradation of PLA/PBAT film is closely related to soil environments and bacterial community. It is significant for the application of biodegradable plastics in agriculture on the perspective of soil sustainability.